UWB Rectangular Slotted Microstrip Patch Antenna In Proximity Of Human Arm Model - Muhammad Syafiq, Noor Azizi; Azahari, Salleh; Adib, Othman; Najmiah Radiah, Mohamad; Nor Azlan, Mohd Aris; Maisarah, Abu; Nornikman, Hassan; Mohamad Hafize, Ramli; Thailis Bounya, Ngelayang (Penerbit UTM Press, 2016)
In this paper, we study behavior of Ultra wideband antenna which is Rectangular Slotted Microstrip Patch Antenna. Then, the antenna operated in proximity of human arm model. Furthermore, the antenna is designed on a FR-4 substrate with dielectric constant of 4.3 and thickness 1.6 mm. This antenna simulated in CST Microwave Studio software. In order to test the antenna, an arm model was numerically modelled. The study shows properties and performances of antenna when it is placed in three situations which in free space, outside and inside of human arm model. The properties of UWB antenna in term of return loss, gain, directivity and radiation pattern in the three situations is simulated and discussed.